PENGARUH KOMBINASI JARAK TANAM, PUPUK TUNGGAL, SERTA PUPUK MAJEMUK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN PADI (Oryza sativa L. ) VARIETAS INPARI 30 - E. Tadjudin; - Alfandi; - Warti (Program Studi Ilmu Pertanian Pascasarjana UGJ, 2016)
This study aimed to determine: (1) the effect of the combination of plant spacing, single fertilizer, and compound fertilizer on growth and yield of rice plants (Oryza sativa L.) Varieties Inpari 30, (2) at a spacing, single fertilizer, and compound fertilizer which one gives the best effect on the growth and yield of rice plants (Oryza sativa L.) Varieties Inpari 30, and (3) the correlation between growth and yield components of rice plants (Oryza sativa L.) Varieties Inpari 30. The experiment was conducted in Mekarsari Village Tukdana District Indramayu District, from March through the month of July 2015. The method used in this study is the experimental method. The experimental design used was a randomized block design (RBD). This experiment consisted of 9 combined treatment plant spacing, single fertilizer, and compound fertilizer, each repeated three times, so there are 27 experimental plots. The combination treatment was tested in the field are: A (spacing 25 cm x 25 cm, 100 kg Urea, SP-36 50 kg, NPK Phosnka 100 kg, and 250 kg of organic fertilizer), B (spacing 25 cm x 25 cm, 200 kg Urea, SP-36 100 kg, NPK Phosnka 200 kg, and 500 kg of organic fertilizer), C (spacing 25 cm x 25 cm, 300 kg Urea, SP-36 150 kg, NPK Phosnka 300 kg, and 750 kg of organic fertilizer), D (legowo spacing of 2:1, 100 kg Urea, SP-36 50 kg, NPK Phosnka 100 kg, and 250 kg of organic fertilizer), E (legowo spacing of 2:1, 200 kg Urea, SP-36 100 kg, NPK Phosnka 200 kg, and 500 kg of organic fertilizer), F (legowo spacing of 2:1, 300 kg Urea, SP-36 150 kg, NPK Phosnka 300 kg, and 750 kg of organic fertilizer), G (spacing 40 cm x 40 cm, 100 kg Urea, SP-36 50 kg, NPK Phosnka 100 kg, and 250 kg of organic fertilizer), H (spacing 40 cm x 40 cm, 200 kg Urea, SP-36 100 kg, NPK Phosnka 200 kg, and 500 kg of organic fertilizer), and I (spacing 40 cm x 40 cm, 300 kg Urea, SP-36 150 kg, NPK Phosnka 300 kg, and 750 kg of organic fertilizer).The results showed that: (1) there are real influence among combinations of plant spacing, single fertilizer, an d compound fertilizer on parameters of high average plants age of 52 days after planting (DAP), number of tillers per hill age of 38, 45, and 52 DAP, root volume age of 38 and 52 DAP, Leaf Area Index, the Rate of Plant Growth aged 38-45 DAP, the number of panicles per unit area, the number of filled grain per panicle, grain weight per panicle and dry harvested per plot, and the weight of dry milled grain per plot, (2) dry milled grain weight per plot the best there is on the teratment combination sapcing 40 cm x 40 cm, 200 kg urea. SP-36 100 kg, NPK Phonska 200 kg, and 500 kg of organic fertilizer which produces 7.76 kg/plot or the equivalent 4.14 tonnes/ha. In addition to the weight of dry milled grain per plot also contained on the best treatment combination spacing 40 cm x 40 cm, 300 kg Urea, SP-36 150 kg, NPK Phosnka 300 kg, and 750 kg of organic fertilizer which produces 7.90 kg/plot or the equivalent 4.21 tonnes/ha, and (3) a significant correlation occurred between plant height age 45 DAP, number of tillers per hill aged 38, 45, and 52 DAP, root volume of 38 and 52 DAP, and Leaf Area Index by weight of dry milled grain per plot.